Buy now : creative marketing that gets customers to respond to you and your product - Cesari, Rick, 1956-; Lynch, Ron, 1966-; Kelly, Tom, 1950 Oct. 8- (Hoboken, N.J. : Wiley, 2011)
'Learn the secrets of direct response marketing with the man who created the George Foreman Grill campaign In today's highly competitive, global marketplace, businesses have to do more than just advertise their products. By taking advantage of the accountable advertising model that direct response has to offer, you can improve your bottom line, build brands, and develop lasting relationships with legions of satisfied customers. In Buy Now!, Rick Cesari reveals twenty-five years' worth of insights and methods, enabling you to make the most of direct response marketing in your business toolkit. Whether you're a business owner, executive, inventor, or marketer, Buy Now! gives you the secrets behind the successful campaigns that catapulted products into millions of homes. Find out how to use direct response to create a'self-funding'marketing campaign Learn the techniques to building offers that will get people to respond to your products Use'high touch' direct response marketing to build brand equity and drive sales at retail Find out why large companies like Johnson & Johnson and Valvoline are using these concepts for their consumer brands Cesari has put more companies on the Inc. 500 list of fastest growing companies than anyone else Buy Now! to launch your products and campaigns to new heights-and connect with customers as never before-with Cesari's market-leading insights.'--
Includes index.
Keywords: Direct marketing; Customer relations